Aminations and arylations by direct C–O activation for the design of 7, 8-dihydro-6H-5, 8-ethanopyrido[3, 2-d]pyrimidines. Issue 32 (28th May 2021) - Laurent, Mazarine; Bostyn, Stéphane; Marchivie, Mathieu; Robin, Yves; Routier, Sylvain; Buron, Frédéric
Abstract : A convenient design of 7, 8-dihydro-6 H -5, 8-ethanopyrido[3, 2- d ]pyrimidines is reported from quinuclidinone, which afforded versatile platforms that were then used to access a variety of original heterocycles. Abstract : The design of some novel disubstituted 7, 8-dihydro-6 H -5, 8-ethanopyrido[3, 2- d ]pyrimidine derivatives is reported. The series was developed from quinuclidinone, which afforded versatile platforms bearing one lactam function in position C -2 that were then used to create C–N or C–C bonds for S N Ar or palladium-catalyzed cross-coupling reactions by in situ C–O activation. The reaction conditions were optimized under microwave irradiation, and a wide range of amines or boronic acids were used to determine the scope and limitations of each method. To complete this study, the X-ray crystallographic data of 7, 8-dihydro-6 H -5, 8-ethanopyrido[3, 2- d ]pyrimidine derivative 49 were used to formally establish the structures of the products.